(untitled) - West, Clare (Oxford, 2012)
These stories offer many different experiences. Some are strange, some are scary, some are sad, some are blackly funny. A few are shocking - when Lin Lin returns home for a funeral, she learns a dark and terrible family secret which may destroy her. Bookworms World Stories collect stories written in English from around the world. These stories are from Australia, Canada, India, Malaysia, Nigeria, Singapore, South Africa, and Trinidad.
Keywords: Short stories.,Reading comprehension,English language,Đọc hiểu; Problems, exercises, etc.,Textbooks for foreign speakers.,Câu hỏi và bài tập